Nanotechnologies for society. New designs and applications of nanosensors and nanobiosensors in medicine and environmental analysis. (7th May 2012) - Chomoucka, Jana; Drbohlavova, Jana; Masarik, Michal; Ryvolova, Marketa; Huska, Dalibor; Prasek, Jan; Horna, Ales; Trnkova, Libuse; Provaznik, Ivo; Adam, Vojtech; Hubalek, Jaromir; Kizek, Rene
One of the areas rapidly gaining popularity in all parts of scientific research is Nanotechnology. The pioneering mechanical and electrical engineering has been overtaken by life sciences including chemistry and biology as well as biophysics and biomedicine. The attractiveness of nanodimensions increases in combination with possible life saving function. Therefore the opportunity of application of nano–size objects such as nanoparticles of various types and nature as drug carriers and/or tumour detecting agents is of great interest and number of research publications devoted to this field is increasing rapidly in last years. The complexity of this field requires combined effort of multidisciplinary teams joining researches with diverse expertise such as engineers, physicists, biologists, chemists as well as medical doctors and clinicians. In this review, short summary of development in the field on nanoparticles and nano–based electrodes as well as new software for treatment of data obtained from the electrodes is shown.